Mobile Broadband: A Key Enabling Technology for Entrepreneurship? - Alderete, Maria Veronica (2017)
This article examines whether mobile broadband can be viewed as an enabling technology for entrepreneurship in developing and developed countries. Evidence shows that mobile telephony is becoming more affordable worldwide. Contrary to fixed broadband, mobile broadband ensures better reach and lower costs and has become the most dynamic platform for bringing ICT benefits to entrepreneurship. A six period panel data analysis, 2007–2012, is estimated for 58 countries. Using the Global Entrepreneurship Monitor's Total Entrepreneurial Activity as the dependent variable, a positive influence of mobile broadband on the entrepreneurial activity is observed. Linking ICT and entrepreneurship is an area in need of more research.